Transarterial chemoembolization of hepatocellular carcinoma in a rat model: the effect of additional injection of survivin siRNA to the treatment protocol. Issue 1 (December 2016) - Vogl, Thomas; Oppermann, Elsie; Qian, Jun; Imlau, Ulli; Tran, Andreas; Hamidavi, Yousef; Korkusuz, Huedayi; Bechstein, Wolf; Nour-Eldin, Nour-Eldin; Gruber-Rouh, Tatjana; Hammerstingl, Renate; Naguib, Nagy
Abstract Background Transarterial chemoembolization is one of the most widely accepted interventional treatment options for treatment of hepatocellular carcinoma. Still there is a lack of a standard protocol regarding the injected chemotherapeutics. Survivin is an inhibitor of Apoptosis protein that functions to inhibit apoptosis, promote proliferation, and enhance invasion. Survivin is selectively up-regulated in many human tumors. Small interfering RNA (siRNA) can trigger an RNA interference response in mammalian cells and induce strong inhibition of specific gene expression including Survivin. The aim of the study is to assess the effectiveness of the additional injection of Survivin siRNA to the routine protocol of Transarterial Chemoembolization (TACE) for the treatment of hepatocellular carcinoma in a rat model. Methods The study was performed on 20 male ACI rats. On day 0 a solid Morris Hepatoma 3924A was subcapsullary implanted in the liver. On day 12 MRI measurement of the initial tumor volume (V1) was performed. TACE was performed on day 13. The rats were divided into 2 groups; Group (A, n = 10) in which 0.1 mg mitomycin, 0.1 ml lipiodol and 5.0 mg degradable starch microspheres were injected in addition 2.5 nmol survivin siRNA were injected. The same agents were injected in Group (B, =10) without Survivin siRNA. MRI was repeated on day 25 to assess the tumor volume (V2). The tumor growth ratio (V2/V1) was calculated. Western blot and immunohistochemical analysis were performed. Results For group A the mean tumor growth ratio (V2/V1) was 1.1313 +/− 0.1381, and was 3.1911 +/− 0.1393 in group B. A statistically significant difference between both groups was observed regarding the inhibition of tumor growth (P < 0.0001) where Group A showed more inhibition compared to Group B. Similarly immunohistochemical analysis showed significantly lower (p < 0.002) VEGF staining in group A compared to group B. Western Blot analysis showed a similar difference in VEGF expression (P < 0.0001). Conclusion The additional injection of Survivin siRNA to the routine TACE protocol increased the inhibition of the hepatocellular carcinoma growth in a rat animal model compared to regular TACE protocol.